A Recurrent FAM83H Mutation in an Extended Colombian Family and Variable Craniofacial Phenotypes - Camila Alvarez; María Andrea Aragón; Yejin Lee; Sandra Gutiérrez; Patricia Méndez; Dabeiba Adriana García; Liliana Otero; Jung-Wook Kim (MDPI AG, 2022)
Amelogenesis imperfecta (AI) is a collection of rare genetic disorders affecting the quantity and/or quality of the tooth enamel. AI can be classified into three major types according to the clinical phenotype: hypoplastic, hypocalcified, and hypomatured. Among them, the hypocalcified type shows the weakest physical properties, leaving rough and discolored enamel surfaces after tooth eruption. To date, mutations in the FAM83H gene are responsible for the autosomal-dominant hypocalcified AI. In this study, we recruited a four-generation Colombian family with hypocalcified AI and identified a recurrent nonsense mutation in the FAM83H gene (NM_198488.5:c.1289C>A, p.(Ser430 *)) by candidate gene sequencing. Cephalometric analyses revealed the anterior open bite that occurred in the proband is not correlated with the AI in this family.